Evaluation of a renewable energy system for residential purposes in rural Trinidad and Tobago, West Indies - Baksh, Aviesha; Boodhan, Monica; Cumberbatch, Edward; Boodlal, Donnie; Maharaj, Rean (Universiti Teknologi MARA, Sarawak, 2025)
As Trinidad and Tobago (TT) navigates the complexities of transitioning its energy mix, the interplay between global climate commitments outlined in the Paris Agreement, combined with efforts to achieve its Nationally Determined Contributions (NDCs) and reduce Greenhouse Gas (GHG) emissions associated with the electricity sector has become increasingly crucial. This case study evaluates the role of Renewable Energy (RE) resources in reducing GHGs in the residential electricity sector of TT. Energy data was utilised to create a simulated load profile of a base model using Hybrid Optimisation Model for Multiple Energy Resources (HOMER) Pro. The base model conducted comparative load analyses simulating various grid-tied and stand-alone RE systems and examined economic and environmental impacts via sensitivity analyses. The simulated 94.9% RE hybrid grid-tied system with a 3 kW wind turbine, 0.96 kW photovoltaics (PV) and 0.69 kW converter performed the best, with the potential to reduce GHGs by 50% (670.535 kg CO2 per year). Simulations incorporating grid sellback and unsubsidised grid purchase prices required larger PV capacity (12 kW) and reduced wind capacity (3 kW), resulting in net CO2 emissions of 682.536 kg CO2 per year). Simulated stand-alone systems require significantly higher RE capacities coupled with energy storage and thus are not financially viable for TT. Lastly, the Levelised Cost of Electricity (LCOE) analysis showed that wind turbines have the greatest impact on GHG savings. These findings are crucial and highlight the potential of RE to reduce GHGs, achieve TT’s NDCs and enhance energy independence, and play a vital role in informing policy.